Pengaruh ekstrak rumput laut (Eucheuma cottoni) terhadap kadar malondialdehid dan spermatozoa tikus (Rattus norvegicus L.) yang diinduksi natrium nitrit - Wirastuti, Dessy Sukma; Sukmaningsih, A S S A; Sudirga, Sang Ketut (Jurnal Biologi Udayana, 2022)
Processed meat products are types of food that are easily damaged. Damaged to meat products due to the presence of microorganisms grew. To overcome this, meat processing companies have added a lot of food additives (BTP), namely sodium nitrite (NaNO 2 ). Excess nitrite accumulation in the body can have an effect on the reproductive system. Research conducted by Pavlova et al. (2017) found that there was a decrease in epididymal weight and a reduction in the sperm count of rats exposed to high NaNO 2 . Eucheuma cottoni seaweed contains antioxidants that can neutralize the oxidative properties caused by NaNO 2. The purpose of this study is know the effect of Eucheuma Cottoni seewead extract on Malondialdehid Level and Spermatozoa of White Rat ( Rattus Norvegicus L.) that induced by NaNO2. The design used was a completely randomized design (CRD) consisting of negatif control treatment (K-), positive control treatment (+), dose treatment 1 (P1), dose treatment 2 (P2) and dose treatment 3 (P3).  The negative control treatment (K-) was given distilled water while the positive control treatment was given sodium nitrite at a dose of 22.5 mg / kg BW. Treatment doses 1,2 and 3 were given a combination method of sodium nitrite and seaweed extract at a dose of 150 mg / kgBB / day (P1), 300 mg / kgBB / day (P2), and 450 mg / kgBB / day (P3). Observations were made by observing the levels of MDA ( Malondialdehyde ) in serum and sperm quality namely integrity of the membrane, viability, motility and morphology of spermatozoa male white rats. Data analysis was carried out through the One Way Anova statistical test and continued with the Duncan test. The results showed that seaweed extract dose of 150 mg/kgBW significantly could decrease MDA ( Malondialdehyde ) levels, increased viability, motility integrity of the membrane and morphology of spermatozoa.